2017
DOI: 10.3892/mmr.2017.6525
|View full text |Cite
|
Sign up to set email alerts
|

CD74-immunoreactive activated M1 microglia are shown late in the gerbil hippocampal CA1 region following transient cerebral ischemia

Abstract: Activated M1 microglia secrete proinflammatory cytokines into damaged brain areas. The present study examined activated M1 microglial morphology and expression in the hippocampal Cornu Ammonis (CA) 1 region, which is vulnerable to transient ischemia. Transient cerebral ischemia was performed for 5 min in gerbils, and neuronal death in the CA1 region following transient cerebral ischemia was confirmed using cresyl violet staining, neuronal nuclear antigen immunohistochemistry and Fluoro-Jade B histofluorescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 37 publications
2
24
0
1
Order By: Relevance
“…There were 15 KEGG pathways significantly enriched in Y1 ( Figure 3F and Supplementary Table S5 ). The qPCR results confirmed that the regeneration-related DEGs csf1ra and cd74b ( Chitu et al, 2016 ; Hwang et al, 2017 ) were upregulated in the lesioned hemisphere ( Figure 3G ) and mpeg1.1 and gfap ( Kroehne et al, 2011 ; Paredes et al, 2015 ) in both hemispheres ( Figure 3H ). Moreover, we observed a remarkable increase in the number of proliferating cells at the ventricular zone of the telencephalon in the lesioned hemisphere, detected by proliferating cell nuclear antigen (PCNA) antibody staining ( Figures 3I,J ).…”
Section: Resultssupporting
confidence: 58%
“…There were 15 KEGG pathways significantly enriched in Y1 ( Figure 3F and Supplementary Table S5 ). The qPCR results confirmed that the regeneration-related DEGs csf1ra and cd74b ( Chitu et al, 2016 ; Hwang et al, 2017 ) were upregulated in the lesioned hemisphere ( Figure 3G ) and mpeg1.1 and gfap ( Kroehne et al, 2011 ; Paredes et al, 2015 ) in both hemispheres ( Figure 3H ). Moreover, we observed a remarkable increase in the number of proliferating cells at the ventricular zone of the telencephalon in the lesioned hemisphere, detected by proliferating cell nuclear antigen (PCNA) antibody staining ( Figures 3I,J ).…”
Section: Resultssupporting
confidence: 58%
“…These conclusions were further confirmed in both a bilateral common carotid artery ligation (Bcca) model and a photothrombotic (PT) stroke model. in the hippocampal ca1 region of the Bcca ligation mice, the M1 microglia marker CD74 was observed to be expressed from day 3 post-ischemic insult and elevated from day 5 post-ischemia (45). additionally, CD16 and iNOS expression levels were identified to be increased in infarct regions at day 42 following Bcca (46).…”
Section: Microgliamentioning
confidence: 99%
“…The animals were randomly divided into eight groups (n = 7 in each group): (1) and 2were the vehicle/sham and ischemia group: each was treated with vehicle (sterilized normal saline; 0.85% w/v NaCl) and underwent sham and ischemia/reperfusion operation, (3) and (4) were the 50 mg/kg YES-10/sham and ischemia group: each was treated with 50 mg/kg YES-10 and given sham and ischemia/reperfusion operation, (5) and (6) were the 100 mg/kg YES-10/sham and ischemia group: each was treated with 100 mg/kg YES-10 and subjected to sham and ischemia/reperfusion operation and (7) and (8) were the 200 mg/kg YES-10/sham and ischemia group: each was treated with 200 mg/kg YES-10 and undergone sham and ischemia/reperfusion operation. The vehicle/sham group was designated as a control group.…”
Section: Administration Of Cmr And/or Ealp Extractmentioning
confidence: 99%
“…With occurrence of the reactive gliosis, both pro-inflammatory and anti-inflammatory responses are triggered following ischemic insults [6]. Especially, pro-inflammatory M1 microglia are predominantly increased and distributed in the hippocampal CA1 field when reactive microgliosis occurs due to cerebral ischemia [7]. In addition, a number of studies have described that enhancement of anti-inflammatory responses can prevent neuronal damage following cerebral ischemic insults [8][9][10].…”
Section: Introductionmentioning
confidence: 99%